Patient-Centered Communication Among Pharmacy Professionals Working in Hospitals and Drug Retail Outlets in Asmara, Eritrea: Knowledge, Attitude, Self-Efficacy and Barriers [Erratum] - Michael E; Nurahmed A; Mihreteab H; Nurhussien M; Adem M; Goitom A; Mihreteab Siele S; Tesfamariam EH; Abdu N (Dove Medical Press, 2022)
Michael E, Nurahmed A, Mihreteab H, et al. Integr Pharm Res Pract. 2022;11:153–164. Page 153, Abstract, Methods, line three, the text “May to June 2021” should read “June to August 2021”.